2013
DOI: 10.3892/ijmm.2013.1438
|View full text |Cite
|
Sign up to set email alerts
|

Viral involvement in the pathogenesis and clinical features of ophthalmic pterygium (Review)

Abstract: Pterygium is a potentially vision-threatening fibrovascular lesion originating from the conjunctiva that often extends on the corneal surface. Although it has been extensively studied, its pathogenesis has yet to be fully elucidated. Recent evidence on molecular genetic abnormalities in pterygium suggested neoplastic changes of limbal stem cells potentially associated with exposure to ultraviolet (UV) light. Human papillomavirus (HPV) is an oncogenic virus, associated with squamo-proliferative lesions of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
0
29
0
6
Order By: Relevance
“…[77][78][79] Previous investigations have analyzed the influence of viruses on pterygium pathogenesis. 11,80,81 From these reports, it was concluded that HPV is the virus most frequently found in pterygium, with prevalence rates ranging from very low up to 100%. According to these reviews, the lowest prevalence of HPV in pterygium samples has been identified in Turkish, Japanese, and Ecuadoran patients (0%, 4.8%, and 21%, respectively), [82][83][84] while the highest prevalence has been reported for Italian, Brazilian, and English patients (100%, 58.3%, and 50%, respectively).…”
Section: Viral Infections and Hereditymentioning
confidence: 96%
“…[77][78][79] Previous investigations have analyzed the influence of viruses on pterygium pathogenesis. 11,80,81 From these reports, it was concluded that HPV is the virus most frequently found in pterygium, with prevalence rates ranging from very low up to 100%. According to these reviews, the lowest prevalence of HPV in pterygium samples has been identified in Turkish, Japanese, and Ecuadoran patients (0%, 4.8%, and 21%, respectively), [82][83][84] while the highest prevalence has been reported for Italian, Brazilian, and English patients (100%, 58.3%, and 50%, respectively).…”
Section: Viral Infections and Hereditymentioning
confidence: 96%
“…A causative role for UV-B radiation is well documented by epidemiological and experimental data; other accepted risk factors include chronic inflammatory processes, alterations in cytokine expression, genetic factors and viruses (Cimpean et al 2013, Moran andHollows 1984;Lee et al 1994;Fox et al 2013;Siak et al 2011;Peng et al 2012;Chalkia et al 2013). Nonetheless, the underlying molecular mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to apply IHC method to identify HPV in pterygia in order to avoid the false‐positive results, which are commonly associated with PCR technique (Chalkia et al. ). Moreover, most people develop immunity against HPV after a period of months or years of the infection and become HPV DNA negative (Onda et al.…”
Section: Discussionmentioning
confidence: 99%